Environmental health and occupational safety - Gupta, Pankaj (Boca Raton, FL : CRC Press, 2024)
"The scope of Occupational Safety and Health (OSH) has evolved gradually and consistently in response to socio-political, scientific, and profitable deviances. In recent years, globalization of the world's economies and its impacts have been recognized as the greatest force for change in the domain of workplace, and accordingly in the scope of occupational safety and health, both in positive and negative ways. OSH is a key element in achieving suitable working conditions and safety cultures. Environmental Health and Occupational Safety is a quick, easy-to-consult comprehensive overview of the issues pertaining to environmental health, OSH. This book equips readers with occupational health risks and hazardous environments encountered in various industrial and workplace settings besides providing basic information on issues related to technology, management, regulatory compliance, and important topics like air, water, and vector-borne diseases. Features: Clearly explains the key concepts of environmental health, and OSH, and explores the benchmarks in the history of OSH. Talks about OSH as a sub-discipline of environmental health and its association with other disciplines. Comprehensive coverage of technical and scientific ideas underlying regulatory requirements and elucidates diverse facets of environmental health and OSH using flow charts and tabulations. The fact file at the beginning of each chapter highlights the key points on the themes covered in the chapter. This book serves as a reference book for advanced students and researchers in the disciplines of environmental sciences, environmental health, eco-toxicology, pharmacology, public health, occupational safety and health, etc., besides industry and government departments dealing with environmental regulations and directives"--
Includes bibliographical references and index.
Keywords: Environmental health; Industrial hygiene; Industrial safety